The Effect of Perceived Service Quality and Perceived Price on Customer Satisfaction Furqon Trans in Sidoarjo - Danish Valentino; Zumrotul Fitriyah (PT Inovasi Pratama Internasional, 2023)
Tight competition between car rental company service providers makes car rental companies compete to improve the quality of their services. One of them is Furqon Trans car rental which is currently developing and wants to provide quality service and affordable prices to ensure customer satisfaction. The purpose of this study was to determine the effect of perceived service quality and perceived price on customer satisfaction of Furqon Trans car rental services. The sample used in this study were customers who had made at least two transactions with Furqon Trans Sidoarjo, with a total of 85 respondents, and were over 18 years old. The sampling technique used is non-probability sampling. The analysis technique used is the Partial Least Square (PLS) method. Based on the results of the research that has been done, it shows that Perceived Service Quality has a positive effect on Customer Satisfaction and Perceived Price has a positive effect on Customer Satisfaction of Furqon Trans in Sidoarjo.